2019
DOI: 10.3389/fcvm.2019.00089
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species (ROS), Intimal Thickening, and Subclinical Atherosclerotic Disease

Abstract: Arteriosclerosis causes significant morbidity and mortality worldwide. Central to this process is the development of subclinical non-atherosclerotic intimal lesions before the appearance of pathologic intimal thickening and advanced atherosclerotic plaques. Intimal thickening is associated with several risk factors, including oxidative stress due to reactive oxygen species (ROS), inflammatory cytokines and lipid. The main ROS producing systems in-vivo are reduced nicotinamide dinucleotide phosphate (NADPH) oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 222 publications
(286 reference statements)
2
70
0
Order By: Relevance
“…Recent studies showed that ROS increases the pyroptosis of VEC that contributes to VEC dysfunction and As progression (Wu et al, 2018;Zhaolin et al, 2019). Lowering oxidative stress injury induced by ROS is considered as a promising therapy to inhibit the progression of As (Burtenshaw et al, 2019).…”
Section: Glutamine Blocks Oxidative Stress Injury Induced By Reactivementioning
confidence: 99%
“…Recent studies showed that ROS increases the pyroptosis of VEC that contributes to VEC dysfunction and As progression (Wu et al, 2018;Zhaolin et al, 2019). Lowering oxidative stress injury induced by ROS is considered as a promising therapy to inhibit the progression of As (Burtenshaw et al, 2019).…”
Section: Glutamine Blocks Oxidative Stress Injury Induced By Reactivementioning
confidence: 99%
“…Vascular NOXs are important ROS generating enzymes and in human vascular cells, NOX1, NOX2, NOX4 and NOX5 are expressed. NOX are transmembrane enzyme complexes with a few regulatory subunits and a core catalytic subunit, except for NOX5 [111] . NOX activation results in the generation of O 2 from molecular oxygen by the transfer of electrons from NADPH [112] .…”
Section: Oxidative Stress In Cvd and Cinmentioning
confidence: 99%
“…NADPH oxidase in humans was thought to be phagocyte specific as the two membrane bound units, gp91 phox and p22 phox form a heterodimer and mediate bacterial killing by generating O 2 (gp91 phox produces a burst of O 2 and p22 phox acts to stabilize gp91 phox , enhancing O 2 production) [113] . P22 phox expression in non-phagocytic cells directed the discovery of NOX1 in non-phagocytic cells which then led to the identification of the other NOX proteins [111] .…”
Section: Oxidative Stress In Cvd and Cinmentioning
confidence: 99%
“…The vascular endothelium plays a pivotal role in vascular permeability, maintenance of vascular tone and pressure, platelet aggregation, and thrombosis (Minami et al, 2019). Endothelial cells can be easily damaged by various factors, such as inflammatory cytokines and reactive oxygen species (ROS), which cause endothelial dysfunction that, in turn, initiate early processes of vascular diseases, including atherosclerosis, hypertension, and peripheral venous disease (Herrera et al, 2010;Burtenshaw et al, 2019).…”
Section: Introductionmentioning
confidence: 99%